2007
DOI: 10.1128/iai.01599-06
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salts Stimulate Recruitment of IpaB to the Shigella flexneri Surface, Where It Colocalizes with IpaD at the Tip of the Type III Secretion Needle

Abstract: Shigella flexneri uses its type III secretion apparatus (TTSA) to deliver invasins into human cells. This TTSA possesses an external needle with IpaD at its tip. We now show that deoxycholate promotes the stable recruitment of IpaB to the needle tip without inducing a rapid burst of type III secretion. The maintenance of IpaB at the needle tip requires a stable association of IpaD with the Shigella surface. This is the first demonstration of a translocator protein being stably associated with the TTSA needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
198
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(205 citation statements)
references
References 14 publications
6
198
1
Order By: Relevance
“…5 Shigella is currently the only pathogen for which each step in the T3SA needle tip complex maturation can be artificially induced to mimic natural maturation. [6][7][8] As a first step of Shigella T3SA maturation, IpaD forms a pentameric structure at the tip of the nascent MxiH needle. 9 In its capacity as an environmental sensor, IpaD detects small molecules such as deoxycholate (DOC), promoting a conformational change in IpaD that results in the recruitment of IpaB, the first translocator, to the maturing T3SA needle tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Shigella is currently the only pathogen for which each step in the T3SA needle tip complex maturation can be artificially induced to mimic natural maturation. [6][7][8] As a first step of Shigella T3SA maturation, IpaD forms a pentameric structure at the tip of the nascent MxiH needle. 9 In its capacity as an environmental sensor, IpaD detects small molecules such as deoxycholate (DOC), promoting a conformational change in IpaD that results in the recruitment of IpaB, the first translocator, to the maturing T3SA needle tip.…”
Section: Introductionmentioning
confidence: 99%
“…9 In its capacity as an environmental sensor, IpaD detects small molecules such as deoxycholate (DOC), promoting a conformational change in IpaD that results in the recruitment of IpaB, the first translocator, to the maturing T3SA needle tip. 7,[10][11][12] IpaB then interacts with cholesterol and sphingolipid rich host cell membranes, which can be mimicked using defined liposomes. 8 The interaction of IpaB with host cells or cholesterol/sphingolipid rich liposomes recruits IpaC, the second translocator, 8,13 to assemble the final T3SA needle tip complex, which results in formation of the translocon pore.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is complex and has recently been reviewed (1, 2), we therefore do not touch on this issue here. After needle completion other proteins are secreted through the needle and assemble at the tip, where they are thought to perform roles in host sensing (9)(10)(11)(12)(13). Activation of the T3SS by host cells results in the secretion of two hydrophobic proteins, which, probably from the tip of the needle, insert directly into the eukaryotic membrane to form an apparatus known as the translocon (13).…”
mentioning
confidence: 99%
“…It was recently reported that IpaB and IpaD, the translocon proteins of Shigella, can be localized on the bacterial cell surface (Olive et al, 2007;Veenendaal et al, 2007). However, the surface localization of PopB and PopD of Pseudomonas, BopB and BopD of Bordetella, and BipB and BipD of Burkholderia have not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Shigella IpaB, a homologue of SipB, is associated with the bacterial envelope (Menard et al, 1994;Mills et al, 1988;Watarai et al, 1995) and can be localized to the Shigella cell surface in the presence of T3SS (Olive et al, 2007). Recently, Johnson et al (2006) have shown that surface localization of IpaB is dependent on the presence of IpaD.…”
Section: Introductionmentioning
confidence: 99%